Effects of prenatal psychotherapies and psychosocial interventions on depressive symptoms, anxious symptoms and stress: a systematic review and network meta-analysis - Huo, Lanting; Yu, Xingfeng; Ma, Yujia; Yang, Lei; Li, Xiaomei (Frontiers in Psychiatry, 2026)
BackgroundPerinatal psychological disorders have a significant impact on maternal and neonatal health. While many psychotherapies and psychosocial interventions have been developed and empirically evaluated for the management of perinatal psychological symptoms, the efficacy of these interventions and the most effective intervention modality remain inconclusive.AimTo assess and compare the efficacy of various perinatal psychotherapies and psychosocial interventions for depressive symptoms, anxious symptoms and stress through a comprehensive systematic review with network meta-analysis.MethodsEleven English and Chinese electronic databases were searched from inception to 30 November 2024. The Revised Cochrane Risk of Bias tool for randomized trials was used to assess the quality of the evidence. Standard pairwise meta-analyses were conducted for direct comparisons using Review Manager 5.3, and network meta-analyses were performed using Stata 16 and ADDIS 1.16.5 for different types of interventions based on random-effects models.DesignSystematic review and network meta-analysis with qualitative and quantitative syntheses were performed to holistically investigate intervention effectiveness.ResultsA total of 85 randomized controlled trials were included in the analysis, 65 of which provided available data for quantitative synthesis. The synthesized results suggest that prenatal psychotherapies and psychosocial interventions tend to be effective in reducing depressive symptoms, anxious symptoms and stress with standardized mean differences (SMDs) of -0.70, -0.81, and -1.05, respectively. Multicomponent interventions (SMD=-1.14), interpersonal psychotherapy (SMD=-0.75), cognitive behavioral therapy (SMD=-0.69), mindfulness-based interventions (SMD=-0.68), and psychoeducation (SMD=-0.14) significantly decreased depression symptoms. Acceptance and commitment therapy (SMD=-1.66), interpersonal psychotherapy (SMD=-1.24), counseling (SMD= -1.13), multicomponent interventions (SMD=-0.86), mindfulness-based interventions (SMD=-0.84), and cognitive behavioral therapy (SMD=-0.81) were effective in alleviating anxiety symptoms. Multicomponent interventions (SMD=-5.74), mindfulness-based interventions (SMD=-1.31), cognitive behavioral therapy (SMD=-1.03), and counseling (SMD=-0.82) appeared to be effective strategies for the management of perinatal stress.ConclusionsPrenatal psychotherapies and psychosocial interventions are effective in reducing depressive symptoms, anxious symptoms and stress. Specifically, multicomponent interventions, counseling, and mindfulness-based interventions are superior for alleviating the symptoms of depressive symptoms, anxious symptoms and stress, respectively. Cognitive behavioral therapy may be a reasonable option that could produce a beneficial effect on all of these prenatal psychological problems.